ANALISIS KELAYAKAN MODUL TEMATIK BAGI SISWA KELAS 1 SDN WANGI I JATIROGO - Arik Umi Pujiastuti (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
Teaching materials are an important component in learning activities. One type of teaching material is a learning module that is used by students to study independently. The learning module contains clear instructions and components. In elementary school, it was found that the teaching materials used were textbooks from the government. Therefore, the aim of the research is to develop a thematic module for grade 1 of elementary school. This research is development research using 4-D model. The feasibility of the developed module is seen from 3 aspects, namely material, language, and design. The average score for stage 1 material aspects was 2.66 or 66.67% and experienced an increase in stage 2 to 3.33 or 83.33%. The average score for the language aspect in stage 1 is 3 or 81.25% and increases to 4 or 100% in stage 2. The average score for the design aspect in stage 1 is 2.23 or 55.75% and increases to 4 or 100% in stage 2. Based on the score obtained, the developed module is very feasible to implement.